(untitled) (Journal of Partial Differential Equations, 2024)
This article investigates the blow-up results for the initial boundary value problem to the quasi-linear parabolic equation with p-Laplacian u_t−∇·( |∇u|^p−2∇u)= f(u), where p≥2 and the function f(u) satisfies α^u_0f(s)ds≤u f(u)+βu^p+γ, u>0 for some positive constants α,β,γ with 0